2021
DOI: 10.1371/journal.pone.0252672
|View full text |Cite
|
Sign up to set email alerts
|

Can UVA-light-activated riboflavin-induced collagen crosslinking be transferred from ophthalmology to spine surgery? A feasibility study on bovine intervertebral disc

Abstract: Background Collagen cross-links contribute to the mechanical resilience of the intervertebral disc (IVD). UVA-light-activated riboflavin-induced collagen crosslinking (UVA-CXL) is a well-established and effective ophthalmological intervention that increases the mechanical rigidity of the collagen-rich corneal matrix in Keratoconus. This study explores the feasibility, safety and efficacy of translating this intervention in reinforcing the IVD. Methods Annulus fibrosus (AF) cells were isolated from bovine IVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…R-UV-CXL has also been studied in the fields of wound healing [ 91 ], skin repair [ 92 ], cardiac valves [ 93 ], and vascular regeneration [ 94 ]. A study by Vasilikos et al on the R-UV-CXL treatment of intervertebral disc (IVD) matrices suggested that this treatment may be a promising tool to reinforce the IVD matrix [ 95 ]. In addition, some other photocrosslinking techniques have also been proposed.…”
Section: Exogenous Collagen Modificationsmentioning
confidence: 99%
“…R-UV-CXL has also been studied in the fields of wound healing [ 91 ], skin repair [ 92 ], cardiac valves [ 93 ], and vascular regeneration [ 94 ]. A study by Vasilikos et al on the R-UV-CXL treatment of intervertebral disc (IVD) matrices suggested that this treatment may be a promising tool to reinforce the IVD matrix [ 95 ]. In addition, some other photocrosslinking techniques have also been proposed.…”
Section: Exogenous Collagen Modificationsmentioning
confidence: 99%
“…Vasilikos et al at Ulm University in Germany have investigated the photochemical crosslinking of intervertebral disc (IVD) employing the system UV-A radiation/riboflavin, at an irradiance of 3 mW/cm 2 . They have shown 29 that the photocrosslinking of IVD led to reduced annular delamination, increase of the peel strength, and a significant increase of Young’s modulus. In another study, 30 the subject was the shoulder’s glenohumeral joint capsule; its laxity is one of the main lesions leading to shoulder instability.…”
Section: Photochemical Crosslinking Of Tendonsmentioning
confidence: 99%